SELF DETERMINATION THEORY AMONG SENIOR CITIZEN: A REVIEW PAPER - Zaini, Nur Hidayah; Wan Hasan, Wan Hasmat; Samuel, Rachel; Nor Talib, Afzan; Jamrus, Farah Nadzirah; Ramly, Fariha Aiza (Jurnal ’Ulwan, 2022)
This article overviews self-determination theory (SDT) relates to wellbeing of senior citizens. The important terminologies and concept pertaining self-determination theory are broadly reviewed. Self-determination theory (SDT) conceptualizes basic psychological needs for autonomy, competence, and relatedness as innate and essential for ongoing psychological growth, internalization, and well-being. Despite a widespread concern with the well-being of elderly people, very little is known about the motivation behind every day behaviours in old age. Malaysia officially became an ageing country in 2020 with the percentage of its population aged 65 and above hitting 7.5% (about 2.4 million of the total population). Malaysia is predicted to be an aged society by 2044, when those aged 65 and above make up 14% of the population. Ageing issues might not look like a remarkably interesting phenomenon for the young and healthy. Suggestions are made for further research and for potential applications.